Expansion of Pharmacy Services During COVID-19: Pharmacists and Pharmacy Extenders Filling the Gaps Through Telehealth Services. (June 2022) - Liu, Catherine; Patel, Khusbu; Cernero, Betsy; Baratt, Yuliya; Dandan, Nadine; Marshall, Olga; Li, Hanlin; Efird, Leigh
Purpose: The Coronavirus 2019 (COVID-19) pandemic created a significant disruption in healthcare. In our health-system located in New York City, the provision of care in the ambulatory care setting moved to a remote model virtually overnight. We describe interventions made during the pandemic to transform ambulatory care pharmacy through expansion of telehealth services.Summary: In March of 2020, the closure of primary care clinics and provider appointment cancellations due to inpatient redeployment created a void. Collaboration with other health care providers and development of standardized telehealth workflows served as a conduit for creating new roles and opportunities for pharmacy team members. Three main interventions where the pharmacy team filled gaps include; (1) Expansion of pharmacist telemedicine visits for high-risk patients to improve access to primary care visits, (2) Partnership with nursing to create a centralized refill call center workflow, (3) Integration of pharmacy extenders into the prior authorization process to prevent medication access issues. Existing collaborative practice agreements for chronic disease management were utilized. A virtual pharmacist model for patient care contributed to an increase in telehealth visits from 51 in 2019 to 2997 total visits in 2020. In addition, the health-system refill call center expanded its services through collaboration with our pharmacy team. Pharmacists and pharmacy interns partnered with nurse practitioners to improve the call center workflow and address the significant increase in refill requests during the outbreak. Furthermore, a prior authorization process was created across multiple ambulatory care clinics to expedite medication access and prevent delays in therapy.Conclusion: Our ambulatory care pharmacy team leveraged technology, innovative workflows, and collaborative teamwork to catalyze a shift in pharmacists' and pharmacy extenders' roles in healthcare delivery to expeditiously meet patients' needs during a pandemic.